2021
DOI: 10.3991/ijoe.v17i05.20009
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Spread of COVID-19 and ICU Requirements

Abstract: <span lang="EN-US">Since December 2019, the world is fighting against coronavirus disease (COVID-19). This disease is caused by a novel coronavirus termed as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This work focuses on the applications of machine learning algorithms in the context of COVID-19. Firstly, regression analysis is performed to model the number of confirmed cases and death cases. Our experiments show that autoregressive integrated moving average (ARIMA) can reliably model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Experimentsperformed by [46,51,53] to predict the vaccination ratesand infected/ death casesfor variouscountries using ARIMA and SARIMA models.…”
Section: Arimamentioning
confidence: 99%
“…Experimentsperformed by [46,51,53] to predict the vaccination ratesand infected/ death casesfor variouscountries using ARIMA and SARIMA models.…”
Section: Arimamentioning
confidence: 99%
“…This study uses an FS technique called the Extratrees Classifier which is a classifier with an ensemble approach and is used for classification and regression problems [40][41][42]. Several studies have found performance improvements when using the Extratrees Classifier [43,44] and obtaining high accuracy values even without parameter tuning [45]. In this study, the FS process was carried out by processing the pre-processed data from the TF-IDF weighting, then processing using the ExtraTreesClassifier module in scikit-learn [46].…”
Section: Figure 3 Google Translation Of Several Examples From the Hea...mentioning
confidence: 99%
“…COVID-19 causes symptoms of fever, lung issues, dyspnea [9], etc. In severe cases, patients need admission to intensive care units [10]. In many countries, COVID-19 has created a massive burden on the healthcare system as the number of ICUs is limited.…”
Section: Introductionmentioning
confidence: 99%